Analysis of Students' Scientific Attitudes in Learning Science in The Campus Teaching Program at SMP Negeri 5 People's Village - Puja Arafah Sitepu; Rusdi Machrizal; Hasmi Syahputra Harahap (JPP (Jurnal Pendidikan dan Pembelajaran), 2024)
The aim of this research is to determine the scientific attitude towards science learning in campus teaching programs for class VIII students at SMP Negeri 5 Kampung Rakyat. The research method used in this research is a descriptive method with a qualitative approach. The results of this research analysis show that four dominant scientific attitudes are seen in science learning in campus teaching programs, namely a curious attitude such as students having a high sense of curiosity about new things so that students are enthusiastic about asking questions. Indicators of respect for facts like students can appreciate and accept the opinions expressed by teachers and friends. Indicators of attitudes of willingness to change views such as students being able to realize changes to a more reasonable view of the facts. Students can convey the results of the discussion according to existing facts. The final indicator is a critical thinking attitude, such as students doubting the opinions or answers of other friends, students asking about learning they have just learned about, and students being able to express their opinions if there are differences in opinion between what the teacher conveys and the opinions of other discussion groups.